2018
DOI: 10.1016/j.mex.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interfacial tension measurement method using axisymmetric drop shape analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The pendant drop method can measure both static and dynamic IFT. This method measures the IFT using an analysis of the drop shape (Bagalkot et al 2018):…”
Section: Ift Measurementmentioning
confidence: 99%
“…The pendant drop method can measure both static and dynamic IFT. This method measures the IFT using an analysis of the drop shape (Bagalkot et al 2018):…”
Section: Ift Measurementmentioning
confidence: 99%
“…The maximum contact angle of 114° was measured for a crude oil droplet when it was immersed in distilled water, which expressed the oil-wet state, according to Fig. 6b (Bagalkot et al 2018). The wettability state of the carbonate pellets was sharply altered to water-wet by adding 500 ppm of the Vitagnus extract at a 44.5° contact angle.…”
Section: Contact Anglementioning
confidence: 99%
“…Several works have been carried out to measure the interfacial tension in CO2-brine, CH4-brine, CO2-brine-CH4 systems at different conditions (Amin et al, 2010;Arabloo et al, 2016;Bagalkot et al, 2018;Barati-Harooni et al, 2016;Chow et al, 2016;Dehghan et al, 2015 Broseta, 2012;Kamari et al, 2017;Kashefi et al, 2016;Khaksar Manshad et al, 2016;Mohammad Salehi et al, 2017;Mutailipu et al, 2018aMutailipu et al, , 2018bPereira et al, 2017;Rashid et al, 2017;Stukan et al, 2012;Yasuda et al, 2015) and the relationship between the interfacial tension and solubility highlighted. These investigations have shown that the forces that exist at the interfaces between two phases or fluids interacting are a function of the densities, the temperature and pressures of the fluids system.…”
Section: Interfacial Tension Measurement (Ift)mentioning
confidence: 99%